PENGARUH BERBAGAI JENIS SKARIFIKASI TERHADAP PERKECAMBAHAN BENIH SAGA (Adenanthera pavonina L) DI PERSEMAIAN PERMANEN BPDAS PALU-POSO - Rosdiana, Rosdiana; Zulkaidhah, Zulkaidhah; Umar, Husain; Wahyuni, Dewi (Universitas Tadulako, 2020)
One of the obstacles in the cultivation of saga plant (Adenantherapavonina L) was saga plant’s seeds (Adenantherapavonina L) have the high dormancy properties, it was caused by the hard seed coat which is impermeable to water. An effort to break the dormancy of the saga seeds coat (Adenantherapavonina L) could be done by scarification. This research was located in PersemaianPermanen BPDAS Palu-Poso which is in the Tadulako University area, Palu, Central Sulawesi from June to August 2019. This research was used Completely Randomized Design (CRD) method with four treatments and ten repetitions. Each repetition consisted of five saga seeds (Adenantherapavonina L). So that the saga seeds needed were 200 seeds. The scarification treatment was given S0 symbol: Without scarification (control), S1: Soaking in a hot water with 100oC temperature for 10 minutes. S2: Cutting on cotyledons, S3: Sanding on all plants of seed surfaces. The treatment of various types of scarification of saga seed germinations (Adenantherapavonina L)very significant effect on germination that is germination, speed of germination and simultaneity of germination. The highest germination, germination speed and simultaneity germination in the S3 treatment, namely sanding on the entire surface of the seed coat.The germination rate of S3 treatment with the highest value was 0.95%. The speed of germination with the highest value was 0.03%. Simultaneity germinated with the highest value of 4.40%. Whereas the lowest germination, germination speed and simultaneity germination were found in S0, that is without treatment (control) with a value of 0.00%.Keywords: Seed, Germination, Adenanthera pavonina L